The glutamate to γ-aminobutyric acid ratio in the posterior insula is associated with pain perception in healthy women but not in women with borderline personality disorder. Issue 11 (November 2019) - Gradinger, Tobias; Sack, Markus; Cardinale, Vita; Thiacourt, Margot; Baumgärtner, Ulf; Schmahl, Christian; Ende, Gabriele
Abstract : Abstract: This study aimed to investigate whether the differences in pain perception between patients with borderline personality disorder (BPD) and healthy subjects (HCs) can be explained by differences in the glutamate/GABA ratio in the posterior insula. In total, 29 BPD patients and 31 HCs were included in the statistical analysis. Mechanical pain sensitivity was experimentally assessed with pinprick stimuli between 32 and 512 mN on a numeric rating scale. The metabolites were measured in the right posterior insula using the MEshcher–GArwood Point-RESolved Spectroscopy sequence for single-voxel magnetic resonance spectroscopy (1H-MRS). The 256- and the 512-mN pinprick stimuli were perceived as significantly less painful by the BPD patient group compared with HCs. No differences were found between groups for the glutamate/GABA ratios. A positive correlation between the glutamate/GABA ratio and the pain intensity ratings to 256- and 512-mN pinpricks could be found in the combined and in the HC group. In the BPD patient group, the correlations between the glutamate/GABA ratio and the pain intensity ratings to 256- and 512-mN pinpricks did not reach significance. In conclusion, the study showed that individual differences in pain perception may in part be explained by the individual glutamate/GABA ratio in the posterior insula. However, this possible mechanism does not explain the differences in pain perception between BPD patients and HCs.